ЛОКАЛЬНЫЕ ОСОБЕННОСТИ СОВРЕМЕННЫХ ЭКЗОГЕОДИНАМИЧЕСКИХ РЕЖИМОВ РУССКОЙ РАВНИНЫ - Бронгулеев В.В.; Жидков М.П.; Макаренко А.Г. (My University, 2002)
The paper deals with application of k-means clustering to the analysis of exogeodynamic regimes. Three different regions of Russian Plain were taken for the analysis and the zoning of each one was made on the basis of nine characteristics: precipitation, amount of woodland, amplitude of neotectonic movements, maximal and minimal heights, depth and density of erosion cutting, intensity of landslides and karst processes. Data were obtained by the grid 5'х10'. We consider the area with close mean values of each characteristic, as an area of specific geomorphic regime, the latter defined by the set of values, significantly discrepant from the others. The regions under consideration have different sets of regimes, which nevertheless have some features in common. In every site the regimes of watersheds with low erosion dissection and of deeply dissected slopes are clearly distinguished.
Keywords: ЭКЗОГЕОДИНАМИЧЕСКИЙ РЕЖИМ; КЛАСТЕРНЫЙ АНАЛИЗ; КОРРЕЛЯЦИОННЫЙ АНАЛИЗ; ПРОЦЕССЫ МОРФОГЕНЕЗА; 551.4.042(470.44+470.45+470.53)